The Relationship Between Variations in the Use of Learning Media and the Learning Activity of Citizens Learning - Putri, Mutiara Pratama; Solfema, Solfema (SAINTIS Publishing, 2019)
This study is motivated by the low active learning of Paket B student in PKBM Iftitah Padang Panjang City. The purposes of this study are: (1) describes variation of media learning uses by tutor, (2) describes the active learning of student in Paket B, (3) describes the correlation between variation of media learning uses by tutor with the active learning of student in Paket B. The type of this research is quantitative correlational. The population of this study amounted to 40 people. The study sample is 75 % of the population that is 30 people, the technique is used stratified random sampling. The collecting data technique uses questioner. The data analysis techniques use a percentage formula and product moment correlation formula. The results of the study show that: (1) variation of media learning uses by the tutor is still low variety categorized, (2) the active learning of student in Paket B is still low categorized. (3) there is a significant correlation between the variation of media learning uses with the active learning of student in Paket B.